Revascularization in diabetic foot ulcer and outcome (Ibrahim Cardiac Medical Journal, 2023)
Background & objective: Diabetes is a major public health problem regionally and globally. The prevalence of diabetes and pre-diabetes in general population of Bangladesh is high. Diabetic foot ulcer is a distressing complication for the patients and his family with lifetime risk for foot ulcers in people with diabetes is very high, which may lead to long time morbidity and loss of limb. The present study was intended to determine the outcome of ongoing treatment modalities in diabetic foot ulcers.Methods:This prospective interventional study was done in Combined Military Hospital Dhaka between Jan 2017 to Jan 2020. During the period a total of 267 diabetic patients with foot ulcer reported to the Cardiovascular Surgery Department. Of them 192 patients were suspected to have ischaemic ulcer and included in the study. Revascularization was done by peripheral angiogram and angioplasty or by open surgery. The outcome variables were ulcer healing, minor and major amputations.Result: Revascularization was done in 141(76.2%) patients – percutaneous angioplasty in 120(85.1%) and revascularization by open surgery in 21(14.9%) patients. A total 44(23.8%) patients were treated conservatively. Among them poor anatomy of vasculature for revascularization was present in 19(10.3%) patients, physical condition not suitable for any interventions in 17(9.2%) patients, extensive gangrene/ulcer of foot needing primary amputation in 8(4.3%) patients. In conservative group (n = 44) ulcer healed in 13(29.5%) patients, not healed for > 1 year in 12(27.5%) patients and in 15(34%) patients, major amputation was needed to control infections and save life. Four patients (9%) died of other comorbid conditions. In revascularization group (n=141), ulcer healed in 110(78%), not healed for > 1year in 7(5%) and in 13(9.2%) patients, major amputation was needed to control infections and save life. Eleven patients died due to other comorbid conditions (7.8%). Overall limb salvage rate at our center was 76.8%.Conclusion: Overall limb salvage rate and ulcer healing rate are much better after revascularization of diabetic foot ulcer. Timely and proper intervention of diabetic foot ulcer can help salvage the limbs and improve quality of life and reduce social burden.Ibrahim Card Med J 2022; 12 (1): 30-34